(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article evaluates the source-studying potential of universal history works written in Arabic and Persian in the systematic analysis of the history of the Samanid state (819–999), which ruled Transoxiana and Khorasan in the 9th–10th centuries. The study comparatively examines data from the works of major historians such as Baladhuri, Tabari, Ibn al-Athir, Utbi, Bayhaqi, and Mirkhwand. The research highlights the structure of Samanid central administration, particularly the formation stages of the Turkic hajib elite, their influence on political life, and their conflicts with viziers through the prism of primary sources. Furthermore, unique facts regarding the activities of Fergana governors and internal palace intrigues reflected in these chronicles are integrated into scientific discourse, making the article highly significant for studying the history of Uzbek statehood and military aristocracy